P3-S7.13 Evaluation of the Affirm VPIII microbial identifications test for the diagnosis of vaginitis and bacterial vaginosis. (10th July 2011) - Maseko, D V; Radebe, F M; Gumede, L; Sewphershad, N Bhojraj; Khumalo, S; Basson, I; Lewis, D
Abstract : Background: Vaginitis and bacterial vaginosis (BV) are the most prevalent causes of vaginal symptoms among women of childbearing age. Diagnosis is based on clinical signs and symptoms, microscopy, pH and the whiff" test, and laboratory performed tests. The Affirm VPIII Microbial Identification test (Becton Dickinson) incorporates non-amplified DNA probes for Candida spp., Trichomonas vaginalis and Gardnerella vaginalis as an indicator for BV. Objective: To compare the Affirm VPIII Microbial Identification test for the detection of Candida spp., Gardnerella vaginalis and Trichomonas vaginalis to graded Gram stain for Bacterial Vaginosis and yeast as well as to an in-house Trichomonas vaginalis PCR (Polymerase Chain Reaction). Methods: In this study, specimens from 191 patients were evaluated. Specimens were collected consecutively from patients with vaginal discharge syndrome presenting at an STI (Sexually transmitted infection) clinic in Gauteng, South Africa between May 2010 and February 2011. Study inclusion was dependent upon the request and collection of both a vaginal swab for Affirm VP III and a second swab to make a smear for Gram staining. A cervical swab specimen was also collected for PCR at the same visit. Graded Gram stain for Bacterial vaginosis and yeast as well as an in-house real-time PCR method on the Rotorgene platform was performed in the laboratory. The sensitivity and specificity of the assay was determined using the graded Gram staining as a gold standard for BV and Candida spp. . The real-time PCR was the gold standard for the Trichomonas vaginalis (TV). Results: Analysis of the Affirm VPIII gave a sensitivity of 98% for BV correctly categorising 80of the 82 BV positive specimens and specificity of 76% correctly identifying 38 of the 50 BV- negative specimens. The Affirm VPIII for Candida yielded a sensitivity of 86% and specificity of 95%. When the Affirm was compared to the Real-time TV PCR the sensitivity was at 45% and specificity at 99%. Conclusion: The Affirm VPIII is an objective system which detects mixed vaginal infections and can be used in any setting. The performance characteristics of the Affirm VPIII for BV and Candida were comparable to those of other published studies. However in this study the Trichomonas vaginalis PCR was used as a gold standard therefore the sensitivity of the Affirm VPII of 45% is similar to that of culture or wet mount.